CASP: a community-aware scheduling protocol. (10th May 2011) - Huang, Ye; Bessis, Nik; Kuonen, Pierre; Hirsbrunner, Beat
The existing resource and topology heterogeneity has divided the scheduling solutions into local schedulers and high-level schedulers (a.k.a. meta-schedulers). Although much work has been proposed to optimise job queue based scheduling, seldom has attention been put on the job sharing behaviours between decentralised distributed resource pools, which in turn raises a notable opportunity to exploit and optimise the process of job sharing between reachable grid dynamically and proactively. In our work, we introduce a novel scheduling protocol named the community-aware scheduling protocol (CASP), which dedicates to disseminate scheduling events of each participating node to as many remote nodes as possible. By means of the proposed protocol, the scheduling process of each received job consists of two phases with awareness of grid volatility. The implemented prototype and evaluated results have shown the introduced CASP is able to cooperate with a variety of local scheduling algorithms as well as diverse types of grids.